Pulsed-wave Doppler ultrasonographical measurements of supra-mammary lymph nodes for diagnosis of bovine mastitis - Risvanli, Ali; Dogan, Halef; Safak, Tarik; Kilic, Mehmet Akif; Seker, Ibrahim (Urmia Univ, 2022)
The aim of this study was to investigate the relationship between mastitis and supramammary lymph nodes in lactating cows in terms of Pulsed-wave (PW) Doppler ultrasonographical measurements. A total of 102 head cows in lactation period were divided into three groups. The cows in which all mammary lobes were California mastitis test (CMT)-negative (n = 27) formed the 1st group; those with CMT-positive mammary lobe (n = 43) formed the 2nd group and the cows with clinical mastitis in at least one mammary lobe (n = 32) formed the 3rd group. In PW Doppler ultrasonography, end-diastolic velocity, systolic peak velocity and time-averaged maximum velocity were measured at the most prominent artery of the lymph node. A quantitative scaling was performed by determining the pulsatile index and resistance index scales based on blood flow parameters. There was no statistically significant difference between the study groups in terms of PW Doppler ultrasonographical measurements of supramammary lymph nodes. In conclusion, the use of PW Doppler ultrasonographic data of the supra-mammary lymph nodes will not provide useful information about the current condition of mastitis in cows. (c) 2022 Urmia University. All rights reserved.
Keywords: Cow; Doppler; Mastititis; Supra-mammary lymph node; Ultrasonography